Income Tax in the Labor Community - Cardenal Montesinos, Sergio (1973)
This article explores the possibility of considering the labor community as a taxpayer within the scope of income tax. In this task, the author presents the characteristics and classes of taxpayers according to the doctrine, with the purpose of establishing a clear definition and questioning the system applied to community income. In this regard, the importance of analyzing whether the labor communities meet the requirements to be taxable persons is highlighted, which implies a detailed review of their legal nature and their participation in the management and direction of the company. Along these lines, the author delves into the nature of these as moral entities representing the collective interests of workers, emphasizing their role in the distribution of benefits and compensation based on labor contribution and length of service. Following this idea, he mentioned that in the tax sphere they are not considered taxpayers, which is why their income is not subject to taxation until the workers receive it under the corresponding participation regime. In summary, the author highlights the need to establish an adequate tax regime for community benefits that considers fiscal interest without harming low-income employees affected by the global income of natural persons.